Comparative analysis between pyrolysis products of Spirulina platensis biomass and its residues - Jamilatun, Siti; Budhijanto, B.; Rochmadi, R.; Yuliestyan, Avido; Hadiyanto, H.; Budiman, Arief (International Journal of Renewable Energy Development, 2019)
Today’s needs of energy are yet globally dominated by fossil energy sources, causing the depletion of non-renewable energy. Alternatively, a potential substitute is the energy of biomass. Spirulina platensis (SP) is a microalgae biomass which, if extracted, will produce solid waste called Spirulina platensis residue (SPR). This research explores the pyrolysis product, produced within the range of 300 – 600 ºC, from the pyrolysis of SP and SPR using fixed bed reactors. The influence of temperature on pyrolysis product’s yield and characteristics are investigated by using mass balance method and gas chromatography – mass spectrometry (GC-MS) technique, respectively. The results from mass balance method present an optimum pyrolysis temperature of 550 ºC to obtain the desired liquid product of bio-oil, presenting the percentage of 34.59 wt.% for SP and 33.44 wt.% for SPR case. Additionally, with the increasing temperature, the char yield decreases for about 30 wt.% and the yield of gas seems to sharp increase from 550 to 600 ºC. These tendencies are both applied for SP and SPR source pyrolysis product. Interestingly, the benefit use as fossil fuel substitute might be derived, thanks to high HHV at the bio-oil product (32.04 MJ/kg for SP and 25.70 MJ/kg for SPR) and also at the char product with of 18.85-26.12 MJ/kg for both cases. The additional benefit come from the high content of C in its char product (50.31 wt.% for SPR and 45.26 wt.% for SP) that might be able to be used as an adsorbent, soil softener or other uses in the pharmaceutical field. ©2019. CBIORE-IJRED. All rights reserved